New monetary services (Divisia) indexes for the post-war U.S - Anderson, Richard G.; Duca, John V.; Fleissig, Adrian R.; Jones, Barry E. (Journal of Financial Stability, 2019)
We construct Monetary Services (Divisia) Indexes at various levels of aggregation (the broadest of which is M4) from the late 1940s through 1967 employing methods designed to permit these historical series to be spliced to corresponding series currently published by the Center for Financial Stability (CFS), which begin in 1967. The annualized growth rate of our MSI M2 during 1947 to 1967 generally lies between the growth rates of conventional M1 and M2, while the growth rate of MSI M3 is below that of conventional M3 over the same period. Using spliced series, we find that the velocities of the MSI exhibit gradual upward trends from the late 1940s through 1978, with distinct upward shifts in the late 1970’s and early 1980’s, while the velocity of conventional M3 trends downward between 1953 and 1982. Using a Fourier demand model, we find elastic substitution between M1 and the non-M1 components of MSI M3 up to 1967, but inelastic substitution between bank and thrift deposits.